Konsep "Satu Tungku Tiga Batu" Sosio-Kultutal Fakfak sebagai Model Interaksi dalam Kehidupan Antarumat Beragama - Daud Alfons Pandie (Societas Dei: Jurnal Agama dan Masyarakat, 2018)
ABSTRACT: In the context of the plurality of religion in Indonesia, efforts to develop the study of "religious harmony" became very important. Unfortunately, the study about this topic still very rare. Since the reform era of information research focusing on aspects of religious harmony with the approach of the survey still small number of group, and its popularity is lower than with the research information related to religious conflicts. This paper is one of the efforts the study of harmony between religious communities in the context of Fakfak on the Province of West Papua. Community objective conditions that reflect the reality of the oneness of the Fakfak between plurality of religion with a determination for unity between the person itself and between people and between place. In terms of ethnic and cultural difference, but not a lot of religious and regional language with dialects into a form that is typical of the history of the Islands. To unite the Fakfak of Papua with the social and religious conditions like that, they make a consensus together to create a cultural system, referred to by the term "one-three-stone stove". One three-stone stove is seen as a cultural system that diabstrakan of concrete events, used to understand things living togetherness in individuals and society. Unity in the cultural system of society this defenseless Fakfak strong adhesive. Moreover, the condition of the community characterized the history of the third entry of the religion at the same time. The concept underlying mindset and setting the matter of integration as a force of ethnic fraternity, although different religions. This cultural system considered that gives direction and orientation to the citizens of the community to establish the same culture of tribal solidarity, harmony, tolerance between ethnic groups, religions, and social. Cultural system called a three-stone stove in public life as a manifestation of the Fakfak idiologi culture, are seen as important and valued so deceived behaviour in life between believers. KEYWORDS: one-three-stone stove, interact, believersÂ